2016
DOI: 10.1021/acsnano.6b01782
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Silver Nanoparticles to Breast Milk and Their Biological Effects on Breast-Fed Offspring Mice

Abstract: Recent rodent studies have shown that nanoparticles are distributed to breast milk, and more-detailed safety information regarding nanoparticle consumption by lactating mothers is required. Here, we used mice to investigate the safety of nanoparticle use during lactation. When Ag and Au nanoparticles were intravenously administered to lactating mice, the nanoparticles were distributed to breast milk without producing apparent damage to the mammary gland, and the amount of Ag nanoparticles distributed to breast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 48 publications
1
40
0
Order By: Relevance
“…50) We consider that this information about the associations among the physicochemical properties and biological effects of nanoparticles could lead to clarification of the regulatory factors that define the biological effects or in vivo/in vitro kinetics of nanoparticles.…”
Section: Associations Among the Physicochemical Properties And Biologmentioning
confidence: 99%
“…50) We consider that this information about the associations among the physicochemical properties and biological effects of nanoparticles could lead to clarification of the regulatory factors that define the biological effects or in vivo/in vitro kinetics of nanoparticles.…”
Section: Associations Among the Physicochemical Properties And Biologmentioning
confidence: 99%
“…Currently, scientific efforts are concentrated on determining the effects of NPs on the female reproductive system and embryo development in vivo. 28,32,34,35,39,[43][44][45][46] Yamashita et al found that silica NPs could penetrate into the rodent placenta and transferred to the fetuses, resulting in structural and functional damages in the placenta as well as the inhibition of fetal growth. 23 Chu et al reported that prenatal exposure to CdTe/CdS QDs could migrate from pregnant mice to their fetuses across the placental barrier, 26 whereas we found that amphiphilic polymer-coated CdSe/ZnS QDs (20 nm) were effectively blocked by the placental barrier in our recent study.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, silver NPs were found in breast milk and in the brains of pups and it was also found that titanium dioxide NPs damaged the tight junction of the bloodmilk barrier. 44,45,47 However, these studies lacked biodistribution profiles of NPs in dams, gastrointestinal examination of NPs in pups, and a systemic growth and development analysis of offspring in the long term.…”
Section: Introductionmentioning
confidence: 99%
“…The first is their ability to cross biological barriers [e.g., blood–brain barrier (8), placental barrier (9), blood–milk barrier (10), and nuclear barrier (11)]. The second is their large surface area per unit mass due to their small particle size.…”
Section: Introductionmentioning
confidence: 99%